Combined Knockout of RIPK3 and MLKL Reveals Unexpected Outcome in Tissue Injury and Inflammation - Moerke, Caroline; Bleibaum, Florian; Kunzendorf, Ulrich; Krautwald, Stefan (Frontiers in Cell and Developmental Biology, 2019)
Necroptosis, initially identified as a backup cell death program when apoptosis is hindered, is a prominent feature in the etiology and progression of many human diseases, such as ischemic injury and sepsis. Receptor-interacting protein kinase 3 (RIPK3) is the cardinal regulator of this cell death modality, recruiting and phosphorylating the executioner mixed lineage kinase domain-like protein (MLKL) to signal necroptosis, which is terminated by cellular plasma membrane rupture and leakage of intracellular contents from dying cells. Experimental data to date indicate that RIPK3 and MLKL are the core machinery essential for all necroptotic cell death responses. By using CRISPR/Cas9 (clustered regularly interspaced short palindromic repeat/CRISPR-associated protein 9) technology, we show that Ripk3 and Mlkl knockout and Ripk3/Mlkl double-knockout in necroptosis-sensitive cell lines extensively block susceptibility to necroptosis in each case to an indistinguishable degree. In vivo studies using Ripk3- or Mlkl-deficient mice validated kidney ischemia reperfusion injury and high-dose tumor necrosis factor (TNF) availability as druggable targets in necroptotic-mediated pathologies. Here, we demonstrate that Ripk3 or Mlkl-deficient mice are protected to a similar extent from kidney ischemia reperfusion injury and TNF-induced toxicity. Remarkably, in contrast to each single knockout, Ripk3/Mlkl double-deficient mice did not have appreciable protection from either of the above necroptotic-mediated pathologies. Paradoxically, the double-knockout mice resembled, in each case, the vulnerable wild-type mice, revealing novel complexities in the mechanisms of inflammation-driven diseases that are due to aberrant cell death.